STRUCTURAL ORGANIZATION OF STROMAL AND PARENCHYMAL COMPONENTS OF RAT TESTES DURING CENTRAL DEPRIVATION OF TESTOSTERONE SYNTHESIS ON THE 180 DAY OF THE EXPERIMENT - Stetsuk, Ye.V.; Akimov, O.Ye.; Shepitko, K.V.; Goltsev, A.N. (World of Medicine and Biology, 2020)
Prolonged central deprivation of testosterone synthesis may lead to biochemical and morphological changes in testes. Influence of prolonged testosterone deficiency on reactive nitrogen and oxygen species production, morphological changes in interstitial endocrinocytes and sustentocytes is not yet fully understood. The number of interstitial endocrinocytes is reduced in comparison with the control group, there are interstitial spaces between the convoluted tubules with a complete absence of interstitial endocrinocytes. Interstitial endocrinocytes are reduced in size, their nuclei are heterochromic. When we studied the structural organization of rat sustentocytes from the experimental group in comparison with the control group, we found that hyperplasia of the elements of the smooth endoplasmic reticulum was observed in the cytoplasm of the sustentocytes. The number of mitochondria in the cytoplasm of the sustentocytes decreased, the electron density of the mitochondrial matrix was lowered, protein structures were present either inside the vacuoles or independently located in the cell cytoplasm. Biochemical studies revealed increased NO production from inducible NO-synthase and development of oxidative stress. Experimental central deprivation of testosterone synthesis with diphereline on the 180th day of the experiment leads to shift of NO synthesis from constitutive NO-synthases to inducible NO-synthase and intensification of oxidative stress due to increase of superoxide anion-radical production and decrease in antioxidant protection.
Keywords: testes; interstitial endocrinocytes; sustentocytes; NO-synthase; iNOS; cNOS; L-arginine; superoxide dismutase; rats.